Reward System For Employee Creativity - Kurniawaty Kurniawaty; Nurfatwa Andriani Yasin (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
This study aims to test the effect of the reward system on the creativity of employees at PT. Telkom Access Makassar Maintenance Unit as many as 80 people using the corelation analysis method. The study found that there is a positive and significant influence of the reaward system (intrinsic and extrinsic) on employee creativity. The largest corelation occurs between creativity and Bonus of 0.925 where bonus is one of the ectrinsic rewards, then the second largest corelation occurs between creativity and learning of 0.681, where this learning is one of the intrinsic rewards. Overall, all indifactors of intristic reward variables and ectrinsic rewards have a positive and significant influence on employee creativity. These findings suggest that intrinsic rewards and extrinsic rewards are significantly related to employee creativity, meaning the likelihood of employees to continue working and be more skilled in the company if employees are adequately paid, promoted at the right time and get the right learning.